Association Between Exercise and Blood Glucose Levels In Diabetic Patients - Eryna Laili Putri (Universitas Airlangga, 2017)
Diabetes Mellitus (DM) is a chronic disease with high prevalence, associated with various debilitating complications and can decreases the quality of life in people with it. It is important for people with DM to doing exercise to control the stability of their blood glucose levels. The purpose of this study was to finding out the association between frequency, duration, and intensity of exercise with average blood glucose levels in people with DM. This was an observational study that used case control design. Data obtained from interview with 20 samples from case group and 20 samples from control group, that had been chosen with systematic random sampling technique. Dependent variable of this study was the average blood glucose levels and independents variables were frequency, duration, intensity, and the kind of exercise. This study used Chi Square test 3 × 2 contingency tables to finding out the association and risk of dependent variable with independent variables,. The results showed that exercise factors that associated to average blood glucose levels were duration of exercise (p = 0.022) and intensity of exercise (p = 0.021). The frequency of exercise does not associated to average blood glucose levels (p = 0.340). Diabetic patients who did not do any exercise have the risk of having uncontrolled blood glucose levels. The conclusion was duration and intensity of exercise related significantly to blood glucose levels. By doing exercise three times a week for 30 minutes or more can decreases the risk of uncontrolled blood glucose levels in people with DM. Keywords: Diabetes mellitus, exercise, average blood glucose levels